Pengukuran, Analisis Hamrmonik Dan Pembetulan Faktor Kuasa - Chew, Hon Wah (Universiti Sains Malaysia, 2006)
Recently, harmonic study in power system received added significance. This is because devices which generate harmonics current are increasing in power system. Harmonics sources are such as power electronic devices and electric arcing devices. The harmonics generated will affect power quality and power system stability. In this project, study of harmonics were carried out at Welding Workshop in School of Mechanical Engineering, University Science Malaysia. There are electric arc welding machines which are the main harmonic sources in the studied location. This study was carried out to improve the power quality of power system and ensure the stability of the system in the plant. The study include harmonic field measurement, harmonic analysis, and filter design work to reduce harmonic distortion. The filter designed is not only used to reduce harmonics current, but also used to improve power factor of the system. In this report, theories of harmonics and power factor was discussed and analytical technique used to correct power factor was presented. It is expected that the improvement of harmonic distortion after installation of proposed filter is from 19.38% to 12.41%, whereas the displacement power factor will achieve 0.90. The technique used in this project can be a reference for improving power quality in other similar plant.